Program KKN Universitas PGRI Kanjuruhan Malang (UNIKAMA) Di Desa Wonokerso Tahun 2024: Inisiatif Pengelolaan Sampah Sebagai Bentuk Peduli Lingkungan - Engelbertus Kukuh Widijatmoko; Sisilia Mayang Sari; Klara Natalia (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) of Universitas PGRI Kanjuruhan Malang (UNIKAMA) for the year 2024 in Wonokerso Village, Pakisaji District, Malang Regency, focuses on communal activities and environmental awareness involving active participation from the village community. The main activities carried out include cleaning the area in front of the village hall, which has been misused as a dumping ground by the local residents. Additionally, UNIKAMA KKN students have created innovative recycling bins in Wonokerso Village as part of their efforts to raise awareness about the importance of maintaining environmental cleanliness. These activities aim to reduce negative impacts on the village's tourism potential and to create a healthier and more pleasant environment. Survey findings indicate that the community still has low awareness regarding environmental issues and limited waste management facilities. The article proposes concrete solutions suggested by the UNIKAMA KKN students, such as the creation of recycling bins and the planting of decorative plants in strategic areas. These solutions are expected to serve as a sustainable initial step towards building environmental awareness and responsibility in Wonokerso Village.